2021
DOI: 10.1183/13993003.03492-2020
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of anti-tuberculosis treatment duration based on a 22-gene transcriptomic model

Abstract: BackgroundThe World Health Organization recommends standardised treatment durations for patients with tuberculosis. We identified and validated a host-RNA signature as a biomarker for individualised therapy durations for patients with drug-susceptible (DS)- and multidrug-resistant (MDR)-tuberculosis.MethodsAdult patients with pulmonary tuberculosis were prospectively enrolled into 5 independent cohorts in Germany and Romania. Clinical and microbiological data, and whole-blood for RNA transcriptomic analysis we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 43 publications
(61 reference statements)
0
14
0
4
Order By: Relevance
“…In this study, we identified peripheral blood transcriptional signatures which predict anti-TB treatment success and failure in TB patients with or without concomitant hyperglycaemia or DM. Previous studies developing biomarker signatures of TB treatment success, recurrence or failure [24][25][26]56 did not include people with DM comorbidity, and we have previously found concomitant DM impairs existing TB diagnosis signature accuracy. 32 Here we showed DM also affects existing TB treatment-response biomarker signatures in the RNA-Seq dataset, suggesting that they should be derived with cohorts including this population.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we identified peripheral blood transcriptional signatures which predict anti-TB treatment success and failure in TB patients with or without concomitant hyperglycaemia or DM. Previous studies developing biomarker signatures of TB treatment success, recurrence or failure [24][25][26]56 did not include people with DM comorbidity, and we have previously found concomitant DM impairs existing TB diagnosis signature accuracy. 32 Here we showed DM also affects existing TB treatment-response biomarker signatures in the RNA-Seq dataset, suggesting that they should be derived with cohorts including this population.…”
Section: Discussionmentioning
confidence: 98%
“…A five-gene signature that correlates with the pulmonary inflammatory state, as measured by PET–CT, identified patients at risk of treatment failure 1–4 weeks after start of therapy 85 . More recently, a 22-gene transcriptomic model that predicts cure-associated end-of-therapy was defined for patients infected with drug-susceptible and MDR M. tuberculosis strains 86 . Developing rapid and affordable point-of-care tests that quantify these biomarkers and deploying assays and adapted treatment guidelines are the major unmet needs.…”
Section: Treatment Challengesmentioning
confidence: 99%
“…Biomarkers to individualise the duration of anti-TB therapies are currently under evaluation. 67 The current recommendation for the duration of PTB treatment with the standard 2HRZ(E)/4HR regimen is 6 months. Monitoring to evaluate treatment response in patients with PTB is recommended; patients should have a repeat sputum for smear and culture at Month 2.…”
Section: Standardmentioning
confidence: 99%